The Impact of Autism On Ethnic Minority Children in Middle and Low-Income Countries: An Under-Researched Challenge - Ndindeng, Atina (Journal of Medical Health Research and Psychiatry, 2024)
Autism Spectrum Disorder (ASD) is a complex neurodevelopmental condition marked by challenges in social communication, restricted interests, and repetitive behaviours. While substantial research has been conducted in high-income countries, the impact of autism on ethnic minority children in middle- and low-income countries (MLICs) is significantly under-explored. This study employs a mixed-methods approach, integrating a systematic review of existing literature with qualitative interviews from selected MLICs, to comprehensively analyse the unique challenges faced by these populations. The findings reveal significant disparities in diagnosis, treatment, and social outcomes, shaped by cultural perceptions, economic factors, healthcare infrastructure, and intersecting identities. Additionally, the study examines broader societal impacts and developmental implications, concluding with a call for targeted research, policy interventions, and community-based strategies to bridge these gaps.